A Comprehensive Systematic Review of the Association Between Airway Mucins and Chronic Rhinosinusitis. Issue 4 (July 2019) - Kato, Kosuke; Song, Brian H.; Howe, Carol L.; Chang, Eugene H.
Objective: Airway mucins are the major constituents of mucus and one of the first lines of host defense against inhaled pathogens. However, aberrant expression of mucins is associated with mucus hypersecretion resulting in chronic nasal drainage, a common complaint from patients with chronic rhinosinusitis (CRS). Our goal in this systematic review was to determine (1) expression profiles, (2) regulatory mechanisms, and (3) the pathologic roles of mucins associated with CRS. Methods: MEDLINE, Cochrane Library, Embase, Scopus, Web of Science, and ClinicalTrials.gov were searched for studies focused on the role of mucins in CRS. Quality was assessed using the Cochrane Risk of Bias tool. The full text articles selected were then categorized into 3 study groups: (1) clinical, (2) animal, and (3) in vitro cultures. Data regarding study design, population/setting, methods, and bias were extracted and synthesized. Results: Our initial search generated 392 titles/abstracts. After the primary review, 111 articles underwent secondary review. The final review included 53 articles, including 34 articles (64%) in the clinical study group, 3 articles (6%) in the animal study group, and 16 articles (30%) in the in vitro study group. In total, aberrant expression of 8 mucins—6 secreted-mucins (MUC2, -5AC, -5B, -6, -7, and -8) and 2 membrane-bound mucins (MUC1 and -4)—were identified in CRS tissues compared to healthy controls. Mucin expression was associated with bacterial sinusitis, inflammatory markers, and the response to steroid therapy in patients with CRS with nasal polyposis. Conclusion: There is a strong correlation between alterations in mucin expression profiles and CRS. This systematic review highlights the most recent literature on the role of mucins in CRS. The analysis of these studies is limited by the heterogeneity in study designs, relatively few numbers of clinical samples, and lack of mechanistic studies in animal models and in vitro cultures.